1994
DOI: 10.1111/j.1439-037x.1994.tb00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Temperature of Irrigation Water on Rice Growth and Nutrient Uptake

Abstract: The study was designed to investigate the effect of cold irrigation water on rice growth and on uptake of N, P, K and Zn applied ca. 50, 20, 35 and 5 mg kg−1 soil, respectively. Cold temperature of irrigation water reduced rice shoot and root dry weight and plant height, significantly compared to hot temperature treatment. Under low temperature stress N was a major rice growth determinant. Increased shoot concentrations of both P and Zn allevated the low temperature stress. The uptake of N, P, K and Zn reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Specifically, positive and non‐additive effects on temperature were the important factor for yield growth rate in oat, sunflower and maize in Uruguay, soybean in Paraná (Brazil), wheat in Córdoba (Argentina) and rice in Maule and Bío Bío (Chile). For example, it has been suggested that warming may prevent the stress of low minimum temperatures at high latitudes like in Chilean rice crops, because freezing may decrease the absorption of water and mineral nutrients (Yoshida, ; Zia et al, ) or reduce plant growth and leaf elongation rates (Sowiński et al, ). The existence of both patterns is not surprising, because the relationship between crop yield growth and temperature could be visualised as a hump‐shaped curve.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, positive and non‐additive effects on temperature were the important factor for yield growth rate in oat, sunflower and maize in Uruguay, soybean in Paraná (Brazil), wheat in Córdoba (Argentina) and rice in Maule and Bío Bío (Chile). For example, it has been suggested that warming may prevent the stress of low minimum temperatures at high latitudes like in Chilean rice crops, because freezing may decrease the absorption of water and mineral nutrients (Yoshida, ; Zia et al, ) or reduce plant growth and leaf elongation rates (Sowiński et al, ). The existence of both patterns is not surprising, because the relationship between crop yield growth and temperature could be visualised as a hump‐shaped curve.…”
Section: Discussionmentioning
confidence: 99%
“…The miR399d expression under the control of rd29A promoter was less than a thousand of that under 35S promoter (data not shown), and its expression level may moderately increase P accumula tion, and it was easy to distinguish between the effect of stresses and P toxicity. Since plants increase P demand under abiotic stresses [2,[4][5][6], the trans genic tomato (C1) has great potential to improve plant growth under these abiotic stresses such as cold and P deficiency.…”
Section: Transgenic Rd29a Ath Mir399d Tomato Improves Growth Under Stmentioning
confidence: 99%
“…Tomato with limited supply of P are more susceptible to chilling [2,6]. Moreover, increased shoot contents of P alleviate the low temper ature stress [2,6]. Therefore, more attention should be paid to the way in which plant response to stress is modified by mineral nutrient supply.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, many studies have payed close attention to the points on rice cultivation, physiological traits, genetics mechanisms and other aspects injuries induced by low temperature stress (Zhang et al 2012;Confalonieri et al 2005;Zia et al 2008) and ooding stress (Mishra et al 2010;Lal et al 2015). Previous studies on ooding mitigating low temperature stress mainly focus on agronomic traits or related physiological characteristics (Farrell et al 2006).…”
Section: Introductionmentioning
confidence: 99%